2012
DOI: 10.1021/ar300072g
|View full text |Cite
|
Sign up to set email alerts
|

The Cation−π Interaction at Protein–Protein Interaction Interfaces: Developing and Learning from Synthetic Mimics of Proteins That Bind Methylated Lysines

Abstract: First discovered over 60 years ago, post-translational methylation was considered an irreversible modification until the initial discoveries of demethylase enzymes in 2004. Now researchers understand that this process serves as a dynamic and complex control mechanism that is misregulated in numerous diseases. Lysine methylation is most often found on histone proteins and can effect gene regulation, epigenetic inheritance, and cancer. Because of this connection to disease, many enzymes responsible for methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 63 publications
3
123
0
1
Order By: Relevance
“…It is known that the trimethylation of lysines may enhance cationelectrostatic (36) and charge independent interactions (37). For example, trimethylation in calmodulin has been shown to modulate NAD kinase (38).…”
Section: Monomethylation Dimethylationmentioning
confidence: 99%
“…It is known that the trimethylation of lysines may enhance cationelectrostatic (36) and charge independent interactions (37). For example, trimethylation in calmodulin has been shown to modulate NAD kinase (38).…”
Section: Monomethylation Dimethylationmentioning
confidence: 99%
“…Several of these receptors bind tighter and more selectively to Kme 3 than native reader proteins, despite being thousands of daltons smaller. [22][23][24][25][26][27] We previously reported one such receptor, A 2 B (Fig. 2), which was found to bind to Kme 3 peptides in aqueous solution with comparable affinity and selectivity to the HP1 chromodomain, a reader protein known to bind histone 3 (H3) K9me 2/3 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the aromatic macrocycle p -sulfonatocalix[4]arene ( 1 ), which mimics the natural aromatic cage of methyl-lysine-binding readers, does not discriminate between peptides containing trimethylated lysine residues and binds H3K4me3, H3K9me3 and H3K27me3 equally well [24]. Furthermore, calix[4]arenes have been known to associate promiscuously with various cationic protein surface sites, which has limited their potential in biological applications up to now [17,25]. In the present study, we report a new set of calixarene-based hosts and show their applicability in characterizing the functions of methyl-lysine-specific epigenetic readers.…”
Section: Introductionmentioning
confidence: 99%